Diversity of helminth parasites in amphibians from northeastern Brazil - Benício, Ronildo Alves; Santos, Rosenilde Silva dos; Freire, Simone Mousinho; Ávila, Robson Waldemar; Silva, Reinaldo José da [UNESP]; Fonseca, Mariluce Gonçalves (Springer Nature, 2022)
Historically, amphibian parasites have been poorly represented in ecological studies, hence, we know little about their diversity, distribution, and role in biological communities. The helminth fauna of four amphibian species (Dermatonotus muelleri, Leptodactylus vastus, Rhinella diptycha, and Trachycephalus typhonius) from three locations in the state of Piauí, northeastern Brazil was studied. In total, we found 2,024 parasite specimens of 13 helminth taxa (Aplectana crucifer, Aplectana vellardi, Cosmocerca podicipinus, Cosmocercidae gen. sp., nematode cysts, nematode larvae, Ochoterenella digiticauda, Ochoterenella sp., Oswaldocruzia lopesi, Oswaldocruzia sp., Oxyascaris oxyascaris, Raillietnema spectans, and Rauschiella linguatula), and ten new occurrences of parasitic helminths were recorded. The most abundant parasite species were R. spectans (n ​​= 1,018) and A. vellardi (n = 574). All hosts presented high infection levels. The prevalence of infection of hosts ranged from 64.7 to 100%, the mean intensity of infection ranged from 6.1 to 69.3, and the mean abundance ranged from 5.5 to 69.3. The number of parasites per host ranged from 122 to 1,468. Dermatonotus muelleri was the host with the highest prevalence of infection (n = 93.9%) and L. vastus presented the highest richness (n = 10 spp.). We also present an update of all helminth species associated with D. muelleri, L. vastus, R. diptycha, and T. typhonius in South America. This is the first study on the diversity of parasitic helminths associated with amphibians in the state of Piauí, northeastern Brazil.
Keywords: Anurans; Neotropical region; Parasitism; Richness; State of Piauí